Factors affecting online food purchase intention : the case of UiTM Terengganu / Siti Hajar Muhd Radzi & Nur Ummaimah Azmi - Muhd Radzi, Siti Hajar; Azmi, Nur Ummaimah (2017)
Online purchase intention is defined as a situation where a consumer is willing and intends to make online transactions. Consumers cannot touch, feel, or try on products before purchase as they have inability to physically examine apparel products directly. The purpose of this study is to investigate the influence of behavioral attitudes towards the social media in the world, Facebook, amongst UiTM students and staffs and their intention whether to purchase or not to purchase online food. This study has examines four factors which are trust, price, convenience, and purchase intention in online food purchasing. This study utilizes a survey approach to gather data regarding the factors of online food purchase. The questionnaires surveys were administered to 150 respondents in UiTM Terengganu. Some analyses had been done which are the frequencies, mean score, standard deviation through the descriptive analysis. The result tells that the factors are reliable for online food purchase and most of the respondents agreed that price and purchase intention is the most factors for online food purchase. So the limitations in this study is about the limited of respondents, time constraint and the final result that only focused for the frequency, mean score and standard deviation. So for the researchers’ suggestion, lantern the time of next study, maximized the respondents to get the best result. So by doing this study, the four factors are acceptable in online food purchase.